1998
DOI: 10.1590/s0100-879x1998000500015
|View full text |Cite
|
Sign up to set email alerts
|

The hyperinsulinemia produced by concanavalin A in rats is opioid-dependent and hormonally regulated

Abstract: The present study examines the effect of concanavalin A (Con A) on the blood insulin and glucose levels of rats. Male and female rats treated with Con A (62.5-500 µg/kg) for three days showed a dose-and time-dependent hyperinsulinemia that lasted more than 48 h. Male rats were more sensitive to Con A. Thus, 6 h after treatment with Con A the circulating insulin levels in male rats had increased by 85% (control: 10.2 ± 0.9 mU/l and Con A-treated: 18.8 ± 1 mU/l) compared to only 38% (control: 7.5 ± 0.2 mU/l; Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Further, Sukumar, Viswambharan (49) identified a NOX enzyme as a contributor in insulin resistance-mediated oxidative stress and postulated that its pharmacological inhibition may possess a novel therapeutic target in insulin resistance-related diseases. In this context, rats injected with ConA showed a significant serum hyperinsulinemia in accordance with FranciscoDoPrado, Zambelli (50). Pretreatment with either apocynin or α-LA significantly counteracted the effect of ConA on serum insulin.…”
Section: Discussionsupporting
confidence: 78%
“…Further, Sukumar, Viswambharan (49) identified a NOX enzyme as a contributor in insulin resistance-mediated oxidative stress and postulated that its pharmacological inhibition may possess a novel therapeutic target in insulin resistance-related diseases. In this context, rats injected with ConA showed a significant serum hyperinsulinemia in accordance with FranciscoDoPrado, Zambelli (50). Pretreatment with either apocynin or α-LA significantly counteracted the effect of ConA on serum insulin.…”
Section: Discussionsupporting
confidence: 78%
“…One study reported limited evidence of sex-based differences in basal transmission and long-term potentiation (LTP) outcomes within male and female rat hippocampal slices following administration of the fast-acting opioid antagonist naloxone (Harte-Hargrove, Varga-Wesson, Duffy, Milner, & Scharfman, 2015), but did note that naloxone enhanced mossy fiber transmission in females during proestrus but not males. A study on hyperinsulinemia (excess insulin relative to glucose) reported that pretreating concanavalin A-injected rats with the opioid antagonists naloxone or naltrexone blocked the hyperinsulinemia produced by lectin in males and females, suggesting that concanacalin A may increase the levels of circulating insulin in rats in a manner that is opioid-dependent and hormonally-regulated (Francisco-DoPrado, Zambelli, Melo-Lima, & Ribeiro-DaSilva, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of the opioid system in lectin activity has already been demonstrated, as in the naloxone‐induced reversion of the antinociceptive effect of lectins from Bryothamnion seaforthii , Bryothamnion triquetrum , and C. boliviana [4,7] and the opioid regulation of hyperinsulinemia by the lectin from Canavalia ensiformis (which is 99% homologous with ConBr) [41].…”
Section: Discussionmentioning
confidence: 99%